Decision making process of job mobility to rural-urban migrant workers: urban survey in the Pearl River Delta of China - Wang, Chunchao; Chen, Guifu; Lu, Yarong (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2013)
This paper attempts to investigate the decision making of job mobility of Chinese rural- urban migrant workers. Based on an analytical framework of decision making of migrant workers, two fundamental hypotheses are proposed: on one hand, the better enterprise-internal working environment has a positive impact on decision making of less job mobility; on the other hand, the better external social environment has a positive impact on the decision of job stability as well. Accordingly, the paper uses empirically a multinomial logit model to analyze the determinants to the decision-making of migrant workers on employment choice based on the field survey in the Pearl River Delta of China. The main empirical findings are as follows: in terms of individual characteristics, those migrant workers who are young or single, or possess a higher degree of education may be more likely to choose job hopping. In particular, a higher level of schooling facilitates increasing the probability of switching jobs by about 14.5%. Second, those migrants who carry the heavy burden of looking after the elderly or children are more likely to job hop. Third, those who have low earnings or those in relatively worse living conditions are more likely to choose job hopping. Finally, some factors of external social environment also make a significant impact on the decision-making of job switching
Argumenta Oeconomica, 2013, Nr 1 (30), s. 85-108
Keywords: job mobility; rural migrant worker; decision making; China’s economy; rynek pracy; migracja zarobkowa